Role of interleukin-21 in primary knee osteoarthritis: a clinical, laboratory and radiological study in Assiut Governorate - Mohamed I.M. Abdelkareem; Awad S. Abbas; Ahmed M. Salem; Rehab A.E. Elsayed (Al-Azhar Assiut Medical Journal)
Background and aim Primary osteoarthritis (OA) is the most frequent arthritis, causing mobility impairment, joint deformities, and compromising quality of life. The objective aimed to evaluate the correlation between the concentration of serum interleukin-21 (IL-21) and the severity of primary knee OA according to stiffness, pain, functional disability, and radiology structural damage in Assiut, Governorate. Patients and methods This case–control investigation has been performed on 300 cases separated into two groups: The patient group: which involved 200 patients diagnosed with primary knee OA and the control group: which involved 100 healthy volunteers. Cases have been collected from those attending the Outpatient clinics of the Rheumatology and Rehabilitation Department, at Al-Azhar University Hospital-Assiut. Results The case group had a significantly greater concentration of serum IL-21 compared with the control group (P=0.004). The Serum IL-21 reference cut-off value obtained from the healthy participants was 0.58 U/ml. A total of 28 cases, accounting for 14% of the sample, exhibited serum IL-21 levels that surpassed the established value of reference cut-off. The serum concentration of IL-21 was significantly elevated in the group of cases with tenderness in the line of knee joint compared with those without knee joint line tenderness (P≤0.001). Conclusion Serum IL-21 might be a potential biochemical indicator for primary knee OA. It could correlate with symptoms and disease progression. Serum IL-21 was significantly greater in cases with primary knee OA. Serum IL-21 was positively associated with Western Ontario and McMaster Universities Osteoarthritis Index stiffness and pain subscale.